A farewell to Tortella bambergeri (Pottiaceae) as understood over the last decades. (3rd July 2017) - Köckinger, Heribert; Hedenäs, Lars
Abstract : Molecular sequence data provide convincing evidence that Tortella bambergeri (Schimp.) Broth., as understood over the last three decades, consists of two species. On the other hand, a careful investigation of the holotype of Trichostomum bambergeri Schimp. revealed its synonymy with Tortella tortuosa (Hedw.) Limpr. (in its current broad sense), which was confirmed by the molecular sequences of two plants from the Alps that were morphologically similar to the T. bambergeri type and that proved to be unrelated to the European plants currently so named. For T. bambergeri auct., two validly described names were located, T. fasciculata (Culm.) Culm., a suboceanic-submediterranean floristic element, and T. pseudofragilis (Thér.) Köckinger & Hedenäs, comb. nov ., a boreo-montane element. Lectotypes for these two names are designated. Beside molecular differences, the two species can be distinguished mainly by having differently shaped cells on the upper leaf margin and by differences in the orientation of the dry leaves. Distribution and ecology of these two taxa are discussed. A key to Tortella (Müll.Hal.) Limpr. species with quadrate superficial cells on the dorsal, upper costa is provided. Hybrid sporophytes in T. pseudofragilis, with T. tortuosa (Hedw.) Limpr. as the male parent, are discussed in the light of other observations, including an apparent hybrid T. pseudofragilis × inclinata from Sweden, suggesting that hybridisation may be important in the evolution within Tortella .